A EFFECT OF WEATHER PARAMETERS ON SEASONAL INCIDENCE OF SAPOTA LEAF WEBBER, NEPHOPTERYX EUGRAPHELLA RAGONOT (LEPIDOPTERA: PYRALIDAE) IN CHHATTISGARH PLAIN - S. K. GHIRTLAHRE,; C. M. SAHU,; Y. P. S. NIRALA, (The Bioscan, 2015)
The field studies revealed that infestation of leaf webber was appeared more or less throughout the year. The minimum leaf infestation of 19.25 per cent was observed during 23 SMW, with 23.0, 18.0, 17.0 and 19.00 per cent leaf infestation in North, South, East and West direction, respectively it increased gradually and reached maximum of 47.5 per cent leaf infestation during 45 SMW with 46.0, 52.0, 41.0 and 51.0 per cent leaf infestation in North, South, East and West direction, respectively. The minimum leaf area infestation of 11.96 per cent was observed during 42 SMW, with 11.03, 13.65, 10.78 and 12.38 per cent infestation in North, South, East and West direction. The maximum leaf area infestation of 40.47 per cent were recorded during 14 SMW with 36.14, 42.71, 45.66 and 37.38 per cent leaf area infestation in North, South, East and West direction, respectively and then dropped down gradually. The correlation studies between leaf infestation and weather parameter revealed that, only minimum temperatures (r = -0.483), average temperatures (r = -0.433) and sun shine hours (r = - 0.384) showed significant negative correlation at 1 and 5 per cent level of significance. Similarly correlation coefficient between leaf area infestation and weather parameter showed that, morning relative humidity (-0.327), evening relative humidity (-0.467), average relative humidity (-0.449) and sun shine hours (-0.360) had significant negative correlation at 1 and 5 per cent level of significance. Maximum leaf damage observed at 23 SMW with average temperature and relative humidity recorded 36.40 oC and 31.60 per cent respectively.